2009
DOI: 10.1162/jocn.2008.21027
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Metabolic Correlates of Episodic Memory in Relation to the Depth of Encoding in Normal Aging

Abstract: This study set out to establish the relationship between changes in episodic memory retrieval in normal aging on the one hand and gray matter volume and (18)FDG uptake on the other. Structural MRI, resting-state (18)FDG-PET, and an episodic memory task manipulating the depth of encoding and the retention interval were administered to 46 healthy subjects divided into three groups according to their age (young, middle-aged, and elderly adults). Memory decline was found not to be linear in the course of normal ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 80 publications
(96 reference statements)
1
21
0
4
Order By: Relevance
“…That is, different LoP at encoding, such as semantic or perceptual analysis of the incoming information, result in more durable traces, therefore affecting the probability of a successful retrieval[34,35]. Although there is some evidence of age affecting LoP[3638], this phenomenon has not been thoroughly investigated in aging. Importantly, it seems that if appropriate support is given during encoding phases (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…That is, different LoP at encoding, such as semantic or perceptual analysis of the incoming information, result in more durable traces, therefore affecting the probability of a successful retrieval[34,35]. Although there is some evidence of age affecting LoP[3638], this phenomenon has not been thoroughly investigated in aging. Importantly, it seems that if appropriate support is given during encoding phases (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Recently developed techniques can obtain measures of grey matter (GM) volume and cortical thickness at the voxel level and permit the correlation study of cognitive function with any brain region, precluding the need for a priori hypotheses. A number of studies have examined the neuroanatomical correlates of cognitive performance using voxel-based measures, such as cortical thickness or GM volume, in healthy adults at different ages [3,7,8]. …”
Section: Introductionmentioning
confidence: 99%
“…One study by Zamboni et al (2013) found a link between HC volume, but not PFC volume, and performance in a visuospatial associative memory task in older adults. However, contrary to the present study, Zamboni and colleagues used incidental learning conditions (see also Kalpouzos et al, 2009). The HC is known for its pivotal role in rapidly forming associations between relational information in long-term memory (Eichenbaum, 2002;Olsen et al, 2012).…”
Section: Structural Differences In Mtl Do Not Account For Individual mentioning
confidence: 66%
“…Structural MRI studies are less conclusive. Equivocal findings have been observed regarding the association between hippocampal volume and item memory (Hackert et al, 2002;Kalpouzos et al, 2009;Köhler et al, 1998;Rosen et al, 2003; for a review see Van Petten, 2004). Structural studies investigating associative memory are generally less common.…”
Section: Introductionmentioning
confidence: 99%